2009
DOI: 10.1097/mop.0b013e3283292614
|View full text |Cite
|
Sign up to set email alerts
|

Update on physical activity including special needs populations

Abstract: Increased physical activity and decreased sedentary behaviors are essential components of obesity management in children with and without disabilities. Pediatric providers are encouraged to address barriers to physical activity with all families and act as advocates for changes in the local community that support access to physical activity for all children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 50 publications
1
10
0
1
Order By: Relevance
“…In female senior high school adolescents, participating in EC activities is associated with improvements in levels of CVD risk factors. The United States Department of Health and Human Services has called for an expansion of school-based EC sports programs to address the obesity epidemic [16,17]. The present study reinforces the premise that participation in school-based EC physical activities has a considerable impact on the levels of multiple CVD risk factors in adolescents.…”
Section: Discussionsupporting
confidence: 88%
“…In female senior high school adolescents, participating in EC activities is associated with improvements in levels of CVD risk factors. The United States Department of Health and Human Services has called for an expansion of school-based EC sports programs to address the obesity epidemic [16,17]. The present study reinforces the premise that participation in school-based EC physical activities has a considerable impact on the levels of multiple CVD risk factors in adolescents.…”
Section: Discussionsupporting
confidence: 88%
“…In females, these values were 108 minutes (95% CI; 91, 129 minutes) in subjects who participated in EC physical activities and 9 minutes (95% CI; 8, 12 minutes) in those who did not participate. The United States Department of Health and Human Services has called for an expansion of school-based EC sports programs to address the obesity epidemic 7,24) . The present study reinforces the premise that participation in school-based EC physical activities has a considerable impact on the levels of multiple CV risk factors in adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Additionally, minimal research has focused on the relationship between physical activity and overweight specifically in children with ASD, although it has been suggested that barriers to physical activity in this group may be related to elevated risk for obesity. 18 Similarly, research has not produced consistent findings on whether autism severity is related to overweight. Ho and colleagues found diagnosis severity to be positively associated with obesity, 17 while Memari and colleagues found overall symptom severity, as well as severity of symptoms in the specific areas of sociability and health and physical behavior, was inversely related to BMI.…”
Section: Introductionmentioning
confidence: 97%